Implementation of Cooperative Learning Techniques to Improve News Text Mastery in Seventh Grade Junior High School Students - Intan Faridatul Munawwaroh; Alfian Rokhmansyah (Jurnal Ilmu Manajemen dan Pendidikan, 2025)
This research aims to analyze the effectiveness of implementing the Cooperative Learning model of Think-Pair-Share type in improving news text mastery among seventh-grade students at SMP Miftahul Arifin. This study employed a Classroom Action Research (CAR) methodology conducted in two cycles, comprising planning, acting, observing, and reflecting stages. The subjects were twenty seventh-grade students at SMP Miftahul Arifin, Probolinggo Regency. Data were collected through learning outcome tests, observation sheets, and motivation questionnaires, then analyzed using descriptive qualitative and simple quantitative methods. The results showed a significant improvement in students' news text mastery. In the pre-cycle phase, the average score was only 64 with 30% mastery. After implementing Think-Pair-Share, the average score increased to 70 (60% mastery) in Cycle I and reached 84 (100% mastery) in Cycle II. Student learning motivation also drastically increased, from 40% of students having high motivation in Cycle I to 70% in Cycle II, with no students having low motivation. This research concludes that the Cooperative Learning model of Think-Pair-Share type is effective in overcoming learning difficulties, improving academic outcomes, and fostering student enthusiasm and active engagement in news text learning.